A Review of Methodological Standards and Current Practices in Hemolytic Toxicity Testing of Nanoparticle-Based Drug Delivery Systems - Yusuf, Mubarika Sekarsari; Nurnahari, Naura (Universitas Muhammadiyah Surakarta, 2025)
Hemolytic toxicity testing is a fundamental component of hemocompatibility assessment for nanoparticle-based drug delivery systems (N-DDSs), as erythrocyte integrity reflects blood safety prior to clinical application. Despite its critical role, experimental procedures vary across the literature. Essential methodological details are frequently omitted, hindering reproducibility and standardization. This variability urges the need for a consolidated reference that examines both current practices and established guidelines. This narrative review aims to provide a structured overview of hemolytic toxicity testing methodologies applied to N-DDSs, with particular emphasis on procedural parameters and their alignment with ASTM and ISO standards. Literature was identified through Google search and open access Scopus-Indexed journals primarily covering publications from 2025 and supplemented with earlier studies to provide historical context. Articles were selected based on relevance to seven methodological parameters which were erythrocyte source, methods of erythrocyte separation and purification, incubation conditions, positive and negative controls, measurement method. Analysis of 30 publications revealed human erythrocytes were the predominant model, with phosphate buffered saline and detergent-like substances were most commonly used negative and positive controls, respectively. Centrifugation controls were inconsistently reported, while incubation was typically run at 37oC, with varying durations depending on the nanoparticle system. Variability was also observed in approaches used to quantify free hemoglobin. Overall, while hemolytic toxicity studies continue to rely on ASTM and ISO guidelines, greater methodological details and standardization would enhance the reliability and reproducibility of hemocompatibility assessments in nanoparticle drug delivery research.